Mental Health from a Qur’anic Perspective: Conceptual Foundations and Implications for Islamic Religious Education - Muhajjalina, Kuunu Ghurron (INCARE, International Journal of Educational Resources, 2026)
Mental health has become a critical issue in contemporary life characterized by social, economic, and technological pressures. This study aims to analyze the concept of mental health from the perspective of Qur’anic values and to examine its contribution to Islamic Religious Education. This research employs a qualitative library research method using thematic analysis of Qur’anic verses related to inner tranquility, supported by classical and contemporary Qur’anic exegesis. The findings indicate that Qur’anic principles—such as recitation of the Qur’an, remembrance of God (dhikr), and piety (taqwa)—play a significant role in fostering inner peace and reducing anxiety. The implications of this study highlight the importance of integrating Qur’anic spiritual values into Islamic Religious Education learning processes as a holistic strategy to develop students’ mental and spiritual well-being, ultimately shaping a generation that is faithful, emotionally healthy, and morally grounded.